FIVE YEARS CHARACTERISTIC OF KIDNEY TRAUMA IN TERTIARY HOSPITAL IN WEST JAVA FROM 2013-2017 - Karim, Ilhamul; Adi, Kuncoro (Indonesian Journal of Urology, 2019)
Objective: Globally, trauma is one of the leading cause of mortality and morbidity. Kidney is an organ that is often affected in trauma cases in urology. This study aimed to determine the characteristics of cases of kidney trauma treated in Hasan Sadikin Bandung Hospital, and used as part of the database of urogenital trauma in Indonesia. Material & Methods: The secondary data was derived from the medical records of patients with kidney trauma treated at Department of Urology in Hasan Sadikin Hospital Bandung for 5 years period (January 2013 to August 2017), as many as 130 cases. Information used was patients’ gender, mechanism of trauma, grading of kidney trauma, associated injury, management, shock, and outcome after treatment. The data obtained was subsequently recapitulated and processed using a spreadsheet. Results: A total 20489 trauma cases admission in Hasan Sadikin Hospital, 477 cases (2.33%) were urogenital trauma, and 130 of which are cases of kidney trauma (0.63%). The majority of patients with kidney trauma are male (87.7%). Based on the mechanism of trauma, 80% of them were related to traffic accidents, especially in motorcycle traffic accidents, as well as the trauma mechanism of falling from a height (13%). There were 69 patients (53.1%) who had major kidney trauma, and 61 patients (46.9%) had minor kidney trauma; specifically, 42.3% grade I and 21.5% grade V kidney trauma. In general, kidney trauma patients experienced multiple trauma, only 19 cases (14.6%) had not associated injury. Most of patients (63%) did not experience shock, and 87.75% of patients survived after treatment. In the timespan of 5 years, 44 patients underwent McAnninch procedure. Conclusion: In Hasan Sadikin Hospital, most cases of kidney trauma were experienced by men, and were caused by blunt trauma in traffic accidents, especially on motorcyclists. Most patients with kidney trauma experienced multiple trauma.